Enhancing circadian clock function in cancer cells inhibits tumor growth. Issue 1 (December 2017) - Kiessling, Silke; Beaulieu-Laroche, Lou; Blum, Ian; Landgraf, Dominic; Welsh, David; Storch, Kai-Florian; Labrecque, Nathalie; Cermakian, Nicolas
Abstract Background Circadian clocks control cell cycle factors, and circadian disruption promotes cancer. To address whether enhancing circadian rhythmicity in tumor cells affects cell cycle progression and reduces proliferation, we compared growth and cell cycle events of B16 melanoma cells and tumors with either a functional or dysfunctional clock. Results We found that clock genes were suppressed in B16 cells and tumors, but treatments inducing circadian rhythmicity, such as dexamethasone, forskolin and heat shock, triggered rhythmic clock and cell cycle gene expression, which resulted in fewer cells in S phase and more in G1 phase. Accordingly, B16 proliferation in vitro and tumor growth in vivo was slowed down. Similar effects were observed in human colon carcinoma HCT-116 cells. Notably, the effects of dexamethasone were not due to an increase in apoptosis nor to an enhancement of immune cell recruitment to the tumor. Knocking down the essential clock geneBmal1 in B16 tumors prevented the effects of dexamethasone on tumor growth and cell cycle events. Conclusions Here we demonstrated that the effects of dexamethasone on cell cycle and tumor growth are mediated by the tumor-intrinsic circadian clock. Thus, our work reveals that enhancing circadian clock function might represent a novel strategy to control cancer progression.